2020
DOI: 10.1007/s11837-020-04155-y
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning in Additive Manufacturing: A Review

Abstract: In this review article, the latest applications of machine learning (ML) in additive manufacturing (AM) field are reviewed. These applications, such as parameter optimization and anomaly detection, are classified into different types of ML tasks, including regression, classification, and clustering. The performance of various ML algorithms in these types of AM tasks are compared and evaluated. Finally, several future research directions are suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
108
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 312 publications
(111 citation statements)
references
References 54 publications
2
108
0
1
Order By: Relevance
“…Therefore, the experimental workload based on conventional trialand-error testing methods and simple orthogonal experiments may substantially increase, undoubtedly substantially increasing the time devoted to research and economic costs. The statistical design of experiments and artificial intelligence prediction methods can be useful in deriving the best process parameters and reducing the volume of actual physical experiments (Goh, Sing, and Yeong 2021;Johnson et al 2020;Meng et al 2020). Rankouhi et al reported the use of machine learning to optimise the processing parameters of L-PBF of the 316L-Cu composite (Rankouhi et al 2021).…”
Section: Challenges In Experimental Methodsmentioning
confidence: 99%
“…Therefore, the experimental workload based on conventional trialand-error testing methods and simple orthogonal experiments may substantially increase, undoubtedly substantially increasing the time devoted to research and economic costs. The statistical design of experiments and artificial intelligence prediction methods can be useful in deriving the best process parameters and reducing the volume of actual physical experiments (Goh, Sing, and Yeong 2021;Johnson et al 2020;Meng et al 2020). Rankouhi et al reported the use of machine learning to optimise the processing parameters of L-PBF of the 316L-Cu composite (Rankouhi et al 2021).…”
Section: Challenges In Experimental Methodsmentioning
confidence: 99%
“…An analytical model was used by Croccolo et al to predict tensile strength based upon build orientation and number of solid shells [18]. A wide range of machine learning techniques have been used in AM [28]. Artificial neural networks (ANNs) were used by Sood et al [12] to predict compressive strength based upon layer thickness, build orientation, raster angle, raster width and air gap.…”
Section: Capability Profilingmentioning
confidence: 99%
“…Above are example methods in ML. In fact, learning is quite a broad topic and several techniques have already been used in 3D printing in general[ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%